PubChem BioAssay: 2017 update. Issue Volume 45:Issue D1(2017) (28th November 2016) - Wang, Yanli; Bryant, Stephen H.; Cheng, Tiejun; Wang, Jiyao; Gindulyte, Asta; Shoemaker, Benjamin A.; Thiessen, Paul A.; He, Siqian; Zhang, Jian
Abstract: PubChem's BioAssay database (https://pubchem.ncbi.nlm.nih.gov ) has served as a public repository for small-molecule and RNAi screening data since 2004 providing open access of its data content to the community. PubChem accepts data submission from worldwide researchers at academia, industry and government agencies. PubChem also collaborates with other chemical biology database stakeholders with data exchange. With over a decade's development effort, it becomes an important information resource supporting drug discovery and chemical biology research. To facilitate data discovery, PubChem is integrated with all other databases at NCBI. In this work, we provide an update for the PubChem BioAssay database describing several recent development including added sources of research data, redesigned BioAssay record page, new BioAssay classification browser and new features in the Upload system facilitating data sharing.